Hubungan Antara Perokok Dan Gammer Terhadap Motivasi Belajar Pada Siswa Taruna Bhakti Cianjur 2021: The Relationship Between Smokers and Gamers on Learning Motivation in Students of Taruna Bhakti Cianjur 2021 - Moch Jodi Selamet (Dohara POAJ, 2022)
Introduction: Learn motivation is very important for the achievement of learning. Learning motivation can be seen in the learning achievement and cognitive aspects of students. Smoking is also one of the negative human habits that have been done for a long time. Aside from the level of addiction in high school students who smoke, students are also often addicted to the name of online games that occur due to peer influence and influence of social environment. Methods: The research used in this study is using quantitative research with correlative design and using the sectional cross, the sampling technique used in this study is the Probability Sampling technique, a sample that will be studied by as many as 100 students. In this study, researchers used questionnaires for smokers and gamers and learn motivation variables. Where in the smoker and gamers questionnaire researchers used 8 questions, and so for the questionnaire motivation learning Researchers also used 5 questions. Statistical test results using the Chi-Square method (x2). Results: The results of statistical tests showed the existence of the relationship between smokers and gamers to learn motivation in Students High School of Taruna Bhakti Cianjur 2021 (p-value = < 0.05) therefore Ho was rejected and Ha accepted. The conclusion is a relationship between smokers and gamers to learn motivation in students of Taruna Bhakti Cianjur 2021. Discussion: The purpose of this study was to find out the relationship between smokers and gamers to learn motivation in High School students of Taruna Bhakti Cianjur 2021.